Detailed crop suitability maps and an agricultural zonation scheme for Malawi: Map files - Benson, Todd; Mabiso, Athur; Nankhuni, Flora (Michigan State University, 2021)
This Research Paper series is designed to timely disseminate research and policy analytical outputs generated by the USAID funded Feed the Future Innovation Lab for Food Security Policy (FSP) and its Associate Awards. The FSP project is managed by the Food Security Group (FSG) of the Department of Agricultural, Food, and Resource Economics (AFRE) at Michigan State University (MSU), and is implemented in partnership with the International Food Policy Research Institute (IFPRI) and the University of Pretoria (UP).